Methodological toolkit as a necessary element of forming professional and communicative competence of cadets – future interal affairs officers - Ryabtseva, Ludmila A. (University Pedagogical Journal, 2024)
In the article the author actualises the problem of developing professional and communicative competence (PCC) of cadets as a future interal affairs officers, emphasising that the presence of the designated competence is a characteristic of an employee capable of defending the interests of society and the state, ensuring the safety of their life. It is proposed to form a cadet’s PCC using the discipline «Criminal law», using methodological tools, the selection of which was made taking into account the essence of the component composition of the PCC. In this regard, the author characterises the specifics of using each individual unit of methodological tools.